High-frequency fabrication of discrete and dispersible hollow carbon spheres with hierarchical porous shells by using secondary-crosslinking pyrolysis. Issue 20 (8th February 2016) - Hong, Min; Chen, Jiafu; Zhang, Minxin; Huang, Xin; Xu, Qun
Abstract : Discrete, uniform HCSs with hierarchical porous shell are fabricated by "secondary-crosslinking pyrolysis", showing high specific capacitance of 192 F g −1 . Abstract : A novel and facile template-free method referred to as "secondary-crosslinking pyrolysis" to fabricate discrete and dispersible hollow carbon spheres (HCSs) with hierarchical porous shells and tailorable shell thicknesses has been successfully developed by using the deformed poly(styrene- co -divinylbenzene) (P(St- co -DVB)) capsules as precursors. The samples are characterized by scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, Raman spectroscopy and N2 adsorption/desorption. Our experimental results indicate that the carbon particles obtained via the designed "secondary-crosslinking pyrolysis" method present a perfect spherical shape and hollow structure, which is dependent on an interesting phenomenon where the deformed P(St- co -DVB) capsules can recover to hollow spheres through the hypercrosslinking reaction. Moreover the obtained HCSs are uniform, discrete and highly dispersible, and more importantly, they have the hierarchical pore structures that can be used as electrode materials for supercapacitors. And the test results indicate that they exhibit a high specific capacitance up to 192 F g −1 at 5 mV s −1, and the formation mechanism behind these phenomena is discussed.